Relationship between uncertainty in illness and hope in patients undergoing haemodialysis in Iran: a cross-sectional study - Seyyede Leila Sajjadi; Maryam Vahidi; Alireza Anarjani Sar; Hossein Nemati (BMJ Open)
Objectives Patients undergoing haemodialysis suffer from uncertainty in illness and hopelessness. The main objective of this study was to examine uncertainty in illness and its relationship with hope in patients undergoing haemodialysis in Iran.Design Cross-sectional study.Setting and participants This study included 202 haemodialysis patients recruited through proportional sampling. Data were gathered using the Mishel Uncertainty in Illness Scale–Community Form and Snyder’s Hope scale. The data were analysed using descriptive statistics and statistical tests including Pearson’s correlation, independent t-test and analysis of variance.Results The mean scores of uncertainty in illness, agency thinking and pathways thinking were 61.91±10.54 (range: 23– 115), 10.30±2.74 (range: 4–16) and 12.04±2.66 (range: 4–16), respectively. The Pearson correlation reflected a significant negative correlation between uncertainty in illness and agency thinking (r=−0.20, p=0.004) and also between uncertainty in illness and pathways thinking (r=−0.21, p=0.002).Conclusions The study found that people with higher education and income, younger age, waiting for a kidney transplant and low uncertainty have more agency and pathway thinking. Therefore, these variables should be worked on. According to the negative association between uncertainty in illness and agency and pathways thinking, well-designed interventions to reduce uncertainty in illness and enhance hope in haemodialysis patients are recommended.